Bacteriophage isolated from non‐target bacteria demonstrates broad host range infectivity against multidrug‐resistant bacteria. (18th August 2021) - Ngiam, Lyman; Schembri, Mark A.; Weynberg, Karen; Guo, Jianhua
Summary: Antibiotic resistance represents a global health challenge. The emergence of multidrug‐resistant (MDR) bacteria such as uropathogenic Escherichia coli (UPEC) has attracted significant attention due to increased MDR properties, even against the last line of antibiotics. Bacteriophage, or simply phage, represents an alternative treatment to antibiotics. However, phage applications still face some challenges, such as host range specificity and development of phage resistant mutants. In this study, using both UPEC and non‐UPEC hosts, five different phages were isolated from wastewater. We found that the inclusion of commensal Escherichia coli as target hosts during screening improved the capacity to select phage with desirable characteristics for phage therapy. Whole‐genome sequencing revealed that four out of five phages adopt strictly lytic lifestyles and are taxonomically related to different phage families belonging to the Myoviridae and Podoviridae . In comparison to single phage treatment, the application of phage cocktails targeting different cell surface receptors significantly enhanced the suppression of UPEC hosts. The emergence of phage‐resistant mutants after single phage treatment was attributed to mutational changes in outer membrane protein components, suggesting the potential receptors recognized by these phages. The findings highlight the use of commensal E . coli as target hosts to isolate broad host range phage with infectivity against MDR bacteria.